Feasibility of Audiovisual Media for Literacy Activities of Students of Grade V in Public Elementary School (SDN) 067241 Medan Denai - Ernayanti, Syafrida; Hadi, Wisman; Saragi, Daulat (BIRCU, 2019)
This study discusses about feasibility of audiovisual media for literacy activities of students of grade V in public elementary school (SDN) 067241 in Medan. This study is conducted in the even semester of Academic Year 2018/2019. The timing of this research is carried out from March to April 2019. The subjects of this study are: (1) students of SDN 067241 Medan Denai class Va as the subject of field trials; and (2) two experts who each have criteria: material experts and media experts. The results shows that a media product of the Tema 4 learning video in the fifth class of Denai Medan. This learning video media product is feasible and valid to be used by Grade V students of SDN 067241 through assessment, revision, and validation from several experts.